Plan de mejoramiento continuo para el proceso de tratamiento de agua potable de la PTAP bellavista ubicada en el municipio de Arbeláez, Cundinamarca (2021)
The objective of this undergraduate project is to propose a continuous improvement plan for the drinking water treatment process of PTAP Bellavista located in the Municipality of Arbeláez, Cundinamarca, which is in charge of the Public Services Office of the Municipality (OSPA). So that the quality of the water that is distributed to a large percentage of the community is benefited, that the changes that are currently being made in the plant (Master Plan) and the changes that are proposed in the future are maintained. The continuous improvement plan is structured using Lean Manufacturing tools and the ADKAR model. Where Lean Manufacturing minimizes waste or loss and activities that do not add any value to the process and uses only what is necessary.